‘I just want to show that I am living a normal life’. Young People with Physical Disabilities on Social Media - Stine Liv Johansen (Nordisk Tidsskrift for Ungdomsforskning)
Numerous young individuals with various clinical diagnoses and disabilities utilise social media and its aesthetic features to amplify their voices and highlight issues related to disabilities. Like other users of social media, young people with disabilities adapt to the genre conventions of the platforms and discuss significant topics, such as apprehensions about hospitals and societal prejudices linked to disabilities. This article scrutinises the utilisation of social media by young people with disabilities to ascertain how they portray themselves on platforms that have frequently faced criticism for perpetuating not only unhealthy body images but predominantly able-bodied ideals as well. The analysis indicates that young individuals consistently contemplate their portrayal on social media and deliberate over what they reveal and to what extent. Concurrently, they purposefully employ social media to challenge prejudice and stigma, both of which they routinely encounter.